Gender, youth and inclusion: Integrating gender across Alliance and CGIAR research - Bioversity International; International Center for Tropical Agriculture (2024)
The "9 Briefs Series" by the Alliance of Bioversity International and CIAT explores critical dimensions of gender, youth, and social inclusion within food, land, and water systems.